Traditional â€œCongklakâ€ Games and Cooperative Character in Mathematics Larning - Kamid, Kamid; Syaiful, Syaiful; Theis, Roseli; Sufri, Sufri; Septi, Sabila Eka; Widodo, Rido Ilham (Jurnal Ilmiah Sekolah Dasar, 2021)
Learning mathematics is a basic material that has been taught since elementary school. However, mathematics is one material that is not liked by the majority of students. In addition to being less attractive, elementary school students also tend to have value gaps among their peers. This indicates a lack of cooperation that is applied in learning mathematics. Therefore, the authors conducted research related to traditional games that were implemented in mathematics learning. The purpose of this study was to determine the relationship and influence of the character of cooperation with students' responses by using traditional games in learning, it is hoped that students are more interested in learning the material, and also traditional games can foster the character of cooperation in students. This type of research uses quantitative methods with the type of comparative research. This research was conducted by distributing questionnaires. The data analysis technique used is random sampling. The research subjects in this study were 120 students at SD IT Ash-Shidiiqi, SD Islam As'ad, and SDN 220/IV Telanaipura Jambi City. The results obtained are SDN 220/IV Telanaipura has a higher percentage than SD IT Ash-Shidiiqi, SD Islam As'ad so that SDN 220/IV Telanaipura has an advantage in the character of cooperation. The conclusion of this study is that there is a relationship and influence of the character of cooperation with student responses.